Simulation and Prototype Design of Hybrid Renewable Energy Harvesting System - Yanuar Zulardiansyah, Arief; Muhammad Syukri, Nurulhak; Hamzah, Eteruddin (Springer Nature Singapore Pte Ltd., 2024)
In this era of globalization, the energy harvesting technology for renewable energy has improved to combat the concerns about energy conservation, global warming, and excessive waste materials. Additionally, the problem of getting continuous and reliable energy and power supply will become a real issue in the future. The energy harvesting technology can be an alternative to the current power generation and can lead to the potential of getting a more reliable power supply for everyone. By combining multiple renewable energy harvesting systems, more power can be continuously generated, and the efficiency of energy output will increase. This paper focuses on the development of a hybrid renewable energy harvester system consisting of photovoltaic, piezoelectric, and wind energy. The system’s performance and capabilities are recorded and analyzed under different conditions and parameters.